Step by step to higher yields? Adoption and impacts of a sequenced training approach for climate-smart coffee production in Uganda - Günther, Manuela Kristin; Bosch, Christine; Ewell, Hanna; Nawrotzki, Raphael; Kato, Edward (Taylor & Francis group, 2025)
Climate change further exacerbates sustainability challenges in coffee cultivation. Addressing these requires effective delivery mechanisms for sustainable farming practices, particularly in smallholder contexts. We assess a novel public-private extension approach in Uganda, called Stepwise, comprising a sequence of climate-smart and good agricultural practices in four incremental steps. Using a mixed-method approach, an index that captures adoption intensity rather than binary uptake, and survey data from 915 Robusta and Arabica coffee farmers, we find adoption levels around 46% and relatively uniform amongst treated, spillover and comparison farmers. Regional variations suggest differing benefits across coffee varieties. Qualitative findings identify barriers to adoption, including financial and labour constraints, suboptimal training delivery, and input and output market imperfections. Despite relatively low uptake, adoption of more than half of the Stepwise practices is associated with substantial gains: inverse probability weighted regression adjustment reveals a 23% increase in yield and a 32% increase in revenue. Our findings add to the adoption literature, which often highlights limited uptake, and have important policy implications. Strengthening producer organizations, delivering targeted training but also innovative solutions for access to inputs and fair pricing, hold considerable potential to increase the adoption of climate-smart practices, particularly among resource-constrained farmers.
Keywords: Climate-smart agriculture; sustainability; coffee valuechain; East Africa; matching; Generalised Poisson; IPWRA